2021
DOI: 10.1111/plb.13234
|View full text |Cite
|
Sign up to set email alerts
|

Effects of heat treatment on metabolism of tobacco plants infected with Potato virus Y

Abstract: Many factors affect successful virus propagation and plant defence responses. Heat shock protein (Hsp) expression after heat shock plays an ambiguous role in viral infection. On the one hand, Hsp70 participates in plant defence response; on the other hand, Hsp70 could interact with viral proteins and facilitate virus propagation.• Here, we studied metabolic adaptations of Nicotiana tabacum L. subjected to heat shock (42°C, 2 h) before or after inoculating the plants with Potato virus Y (potyvirus). RT-qPCR and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 62 publications
(121 reference statements)
1
10
0
Order By: Relevance
“…They postulated that PVY 0 exerted no notable effects on the heat-stress response in resistant plants, whereas in susceptible hosts, PVY 0 infection induced the HSP signaling pathway and modulated the HSP response triggered by heat stress. Hýsková et al [90] observed that the application of heat shock before or after inoculation of the Petit Havana tobacco with PVY accelerated the propagation of infection.…”
Section: Discussionmentioning
confidence: 99%
“…They postulated that PVY 0 exerted no notable effects on the heat-stress response in resistant plants, whereas in susceptible hosts, PVY 0 infection induced the HSP signaling pathway and modulated the HSP response triggered by heat stress. Hýsková et al [90] observed that the application of heat shock before or after inoculation of the Petit Havana tobacco with PVY accelerated the propagation of infection.…”
Section: Discussionmentioning
confidence: 99%
“…References: 1–2, Liebrand et al (2012 , 2014 ); 3, Nekrasov et al (2009) ; 4–5, Park et al (2010 , 2014 ); 6, Nagashima et al (2014) ; 7, Poór et al (2019) ; 8, Wang et al (2005) ; 9, Carvalho et al (2014) ; 10, Qiang et al (2012) ; 11, Xu et al (2012) ; 12, Kanzaki et al (2003) ; 13, Noël et al . (2007) ; 14, Thao et al (2007) ; 15, Nakashima et al (2008) ; 16, Shirasu (2009) ; 17, X.-C. Zhang et al (2015) ; 18, Jing et al (2016) ; 19, Zhou et al (2021) ; 20–21, Jelenska et al (2007 , 2010 ); 22, Lee et al (2018) ; 23, Kim and Hwang (2015) ; 24, Hýsková et al (2021b) ; 25, Ye et al (2011) ; 26, Černý et al . (2016) ; 27, Krishnakumar et al (2017) .…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, a positive effect of HSP70s on viral replication was reported for Chinese wheat mosaic furovirus ( Yang et al , 2017 ) and Cowpea severe mosaic virus ( Paiva et al , 2016 ; Varela et al , 2017 ), and indicated for Tomato bushy stunt virus ( Pogany et al , 2008 ). Further, Nicotiana tabacum plants exposed to heat shock and inoculated with Potato virus Y showed higher amounts of HSP70 genes and higher virus content than the corresponding controls inoculated at standard temperature ( Hýsková et al , 2021b ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hýsková et al . (2021) found that heat shock and subsequent HSP70 expression (especially cytoplasmic and mitochondrial isoforms) accelerate the systemic propagation of viruses in plants by inducing metabolic changes in levels of phenolic acids, glycosides and enzymes of the Hatch‐Slack cycle.…”
mentioning
confidence: 99%